2022
DOI: 10.3390/pharmacy10060140
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacists’ Beliefs about Suboptimal Practice during the Times of COVID-19

Abstract: Introduction: Community pharmacies are high-performance workplaces; if the environment is not conducive to safe practice, mistakes can occur. There has been increasing demand for pharmacists during the COVID-19 pandemic as they have become integral to the response. Suboptimal practices in the work environment and with pharmacists and their teams can impact the safe delivery of services. New Zealand pharmacists’ perceptions of the current work environment and beliefs around whether suboptimal practice have incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The study was undertaken using a mixed methods approach in a similar manner to the previous publication to answer a query about suboptimal practice in the New Zealand setting [ 17 ]. The study gathered data by having registered New Zealand pharmacists complete an anonymous online Qualtrics TM XM survey.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was undertaken using a mixed methods approach in a similar manner to the previous publication to answer a query about suboptimal practice in the New Zealand setting [ 17 ]. The study gathered data by having registered New Zealand pharmacists complete an anonymous online Qualtrics TM XM survey.…”
Section: Methodsmentioning
confidence: 99%
“…The survey was available from 1 October 2021 until 30 November 2021. No further reminders of the survey were emailed, and no follow-up non-responder bias was examined [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Workforce related issues were hypothesized by Wong et al as a potential solution for suboptimal pharmacy practice. 70 In 2022, Wong et al found that 79.8% of pharmacists surveyed reported an increase in the suboptimal practice of pharmacy over the previous five years. 70 …”
Section: Current State Of Pharmacy Workplace Well-being In the Litera...mentioning
confidence: 99%
“… 70 In 2022, Wong et al found that 79.8% of pharmacists surveyed reported an increase in the suboptimal practice of pharmacy over the previous five years. 70 …”
Section: Current State Of Pharmacy Workplace Well-being In the Litera...mentioning
confidence: 99%